Why Integrate Evolutionary and Functional Aspects in Bird Studies in Converted Habitats? - Lucilene, Ines Jacoboski (International Ornithology, 2018)
This essay argues for integrating evolutionary and functional perspectives in bird studies within converted habitats. It highlights how behavior, morphology, and phylogeny interact under land-use change.